2005
DOI: 10.1111/j.1442-9993.2005.01530.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult free zones in small mammal populations: response of Australian native rodents to reduced cover

Abstract: Cover provides shelter, food, nesting opportunities and protection from predators. The behavioural response of small mammals to reduced cover has been well documented. However, very little is known about the effect of cover on community and population dynamics. Australian small mammals generally inhabit extremely dynamic ecosystems, where cover and food supplies are greatly affected by fire. Species are described as early or late seral specialists, generally returning to a disturbed area once their habitat req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 46 publications
(63 reference statements)
0
30
1
Order By: Relevance
“…The characteristics of habitat fragments may be significantly altered by processes including edge effects and anthropogenic disturbances (Saunders et al 1991;Hobbs 2001;Kupfer et al 2006;Fischer and Lindenmayer 2007). Changes to vegetation characteristics can dramatically influence the suitability of sites for fauna (Spencer et al 2005;Luther et al 2008). Thus, the distribution of species in modified landscapes is likely to be influenced by both local habitat characteristics and biogeographic parameters (Thomas et al 2001;Fleishman et al 2002;Armstrong 2005).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The characteristics of habitat fragments may be significantly altered by processes including edge effects and anthropogenic disturbances (Saunders et al 1991;Hobbs 2001;Kupfer et al 2006;Fischer and Lindenmayer 2007). Changes to vegetation characteristics can dramatically influence the suitability of sites for fauna (Spencer et al 2005;Luther et al 2008). Thus, the distribution of species in modified landscapes is likely to be influenced by both local habitat characteristics and biogeographic parameters (Thomas et al 2001;Fleishman et al 2002;Armstrong 2005).…”
mentioning
confidence: 98%
“…Fragmentation causes two key changes to the spatial attributes of habitat that, in turn, have detrimental consequences for fauna: (1) a reduction in the size of habitat fragments, and (2) an increase in the distance between fragments (Saunders et al 1991;Fischer and Lindenmayer 2007). As fragments become smaller, animal populations decline in size, resulting in an increased risk of extinction (Soulé 1987). Isolation restricts interfragment movements, thereby reducing the likelihood of population supplementation and colonisation of unoccupied habitat.…”
mentioning
confidence: 99%
“…The 50% reduction in availability of grass-trees at Site 2 compared with Site 1 did not seem to make any difference in selection of grass-trees by bush rats for cover. Spencer et al (2005) also found that bush rats relied on grass-trees for shelter. These authors reduced the total cover available from X. johnsonii by over 45% by tying overhanging foliage of grass-tree canopies in tight clumps close to the stem of the plant.…”
Section: Discussionmentioning
confidence: 93%
“…Spencer et al (2005) noted that the abundance of Rattus fuscipes (southern bush rat) decreased with a reduction in cover of X. johnsonii on Fraser Island. The study by Spencer et al (2005) and brief mentions of animal and grass-tree associations in other papers validated the need for a detailed study of the role of grass-trees as refuges for wildlife in the Mount Lofty Ranges.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation